Effects of an algae-modified montmorillonite clay on growth performance of nursery pigs fed diets contaminated with low levels of deoxynivalenol - Fowler, Suzy Q.; Frobose, Hyatt L.; Tokach, Michael D.; DeRouchey, Joel M.; Dritz, Steven S.; Goodband, Robert D.; Nelssen, Jim L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2015)
A total of 360 barrows (PIC 1050; initially 25.1 lb and 45 d of age) were used in a 21-d growth trial to evaluate the effects of an algae-modified montmorillonite clay (AMMC) on nursery pig performance when fed diets contaminated with low levels of deoxynivalenol (DON). Pigs were allotted to pens by weight, and pens were randomly assigned to 1 of 9 dietary treatments arranged in a 3 × 3 factorial with main effects of DON (0, 1.5 ppm, or 3.0 ppm) and AMMC inclusion (0, 0.17%, or 0.50% ). There were 5 pigs per pen and 8 pens per treatment. Mycotoxin analyses were conducted on the main ingredients at NDSU3 and LDA Labs4, and the results were used in diet formulation. Naturally contaminated wheat (6.03 ppm DON) was used to produce diets with desired DON levels. No significant DON × AMMC interactions were observed during the entire study. Overall (d 0 to 21), increasing DON concentration in the diet decreased (1.22 vs. 1.10 vs. 1.07 lb; linear, P < 0.001) ADG and d-21 BW as a result of decreased ADFI (2.13 vs. 2.05 vs. 2.11 lb; quadratic, P < 0.01) and poorer feed efficiency (1.49 vs. 1.50 vs. 1.64; linear, P < 0.001). As expected, DON-related growth reductions were most marked from d 0 to 7 (15 to 22% lower) and least distinct in the final period, d 14 to 21 (5 to 6% lower). Incorporating AMMC at increasing levels had no effect on ADG, ADFI, feed efficiency, or final BW. Overall, the results of this study reinforce prior research showing that even low levels of DON significantly reduce nursery pig growth, but the addition of AMMC does not offset the deleterious effects of DON.
Swine Industry Day, 2014 is known as Swine Day, 2014
Keywords: Deoxynivalenol; Montmorillonite clay; Nursery pig; Vomitoxin